A RARE CASE OF A PAEDIATRIC DEATH DUE TO INTESTINAL PERFORATION SECONDARY TO AIR COMPRESSOR - Ratadiya, Prashant M; Vadgama, Divyesh; Parekh, Utsav; Gupta, Sanjay (Journal of Forensic Medicine and Toxicology, 2025)
Intestinal perforation, defined as a loss of continuity of the bowel wall, is a potentially devastating complication that may result from a variety of disease processes. Abdominal trauma, instrumentation, inflammation, infection, cancer, ischemia, and blockage are among the common causes of perforation. The morbidity and possible death of peritonitis, as well as its systemic after effects due to the leakage of intestinal contents, must be avoided by early detection and swift treatment1. Intestinal perforation in children is a rare, acute and life-threatening condition. The incidence of intestinal perforation is 1% to 7% in paediatric trauma patients.2 Colonic barotraumas are caused by pressure increase inside the intestinal lumen.3 The two probable results of colonic barotrauma are colonic mucosal injury and perforation.4 The most dangerous complications of air entry into the rectum at a high volume and velocity in a short time are sigmoid colon rupture and pneumoperitoneum.5 The combination of findings predisposes a patient to perforation of the intestine, secondary to an air compressor, which carries a high mortality rate. Hence the postmortem must be done with a thorough investigation to find out the exact cause of death. The causes of intestinal perforation are many, but due to air compressor is a unique case found in a 4-year old male child.